(3GdLQGFe GdeQJcHI YHQ GdEfJQfJ (B/ s - (3CMeO acQi Wgs; (3CMeO YhV HdGd s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s, 2018)
(3JSJhLH OQGSI XGgQI GdLQGFe GdeQJcHI YHQ THcI GdEfJQfJ GdJYQa Ydi GdCOhGJ GdJi JQJcH HhGSWJgG gPg GdLQGFe ;dGJUGd gPG GdfhY ef GdLQGFe HJcfhdhLjG GdMGSH GdBdi, hGdEfJQfJ MjK EfgG PGJ WHjYI NGUI JJYdb HGdbGfhf GdLfGFi GdeYdheGJi , hGdJi JYJeO HTcd CSGSi Ydi eYGdLI GdeYdheGJ , hGdHjGfGJ EdcJQhfjkG , ajLH GdJYQa ChdkG Ydi eGgjI GdceHjhJQ , hGdEfJQfJ (B. (3aJHQR CgejI OQGSI gPG GdehVhY eYQaI eOi caGjI GdfUhU GdLfGFjI GdMGdjI dehGLgI gPg GdXGgQI ef GdLQGFe GdeSJMOKI HXghQ JcfhdhLjG GdEfJQfJ , hQOY eQJcHjgG Ce dGHO ef GSJMOGK JTQjYGJ LOjOI dehGLgI gPg GdLQGFe (B. (3hJKjQ gPg GdXGgQI ef GdLQGFe CjVG eOi SQjGf bGfhf GdYbhHGJ ef MjK GdecGf , hGdeJeKd ai eOiGfWHGb GdbGfhf GdLfGFj GdOGNdj Ydi GdLQGFe GdJi JQJcH ai GdNGQL ; EPG JMbb HYV ef YfGUQgG Ydi Ebdje GdOhdI(B. (3h jgOa GdHMK HTcd NGU Edi JMbjb YOI CgOGa JJeKd aj VQhQI EdbGA GdVhA Ydi WGFaI ef GdLQGFe PGJ WHjYI NGUI(B: (3hgi GdLQGFe GdeQJcHI YHQ THcI GdEfJQfJ (B: (3hGdJj JbJVi GdJWQb Edi HjGf JYQjagG s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb, (B2018(3, bSe GdbGfhf GdLfGFj s
(3HHdjhLQGajG(B: (3UaMGJ (B368-390 s
Keywords: (3GdeYdheGJjIs; (3LQGFe GdMGShHs; (3GdLQGFe GdeSJMOKIs; (3GdLQGFe GdJcfhdhLjIs; (3GdeLQe GdeYdheGJjs; (3LQGFe GdJbfjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs